The Individual in Family-Orientated Care: A paradox? - C. van Deventer (South African Family Practice)
Although the presence of all family members is the ideal, if one works within the framework of systemic thought and understands that this is the key to interacting with an individual with all the "shadows" that he/she brings, there is no paradox in becoming involved with someone in a stuck situation whether all the role players are present or not. It needs a commitment by are family physician to think systemically all the time and to become skilled at methods that assist this world view. Many of these skills fit well within a narrative way of dealing with family problems.